Cells of Epithelial Lineage Are Present in Blood, Engraft the Bronchial Epithelium, and Are Increased in Human Lung Transplantation - May, L.A.; Kicic, Anthony; Rigby, P.; Heel, K.; Pullen, T.L.; Crook, M.; Charles, A.; Banerjee, B.; Ravine, D.; Saxena, A.; Musk, M.; Stick, S.M.; et al. (ELSEVIER SCIENCE INC, 2009)
Background: There is a growing expectation that cell-based therapies will prove effective for a wide range of conditions including lung diseases such as cystic fibrosis. The promise of these therapies will depend largely on effective delivery and engraftment. In this study, in the setting of human lung transplantation, we sought to determine whether exogenous epithelial cells are able to engraft the transplanted organ and if cells of a similar phenotype could be detected in peripheral blood. Methods: Cells obtained from bronchial brushings and peripheral blood were analyzed via dual fluorescent in situ hybridization/fluorescent immunohistochemistry (FISH/IHC), short tandem repeat polymerase chain reaction (STR-PCR) and flow cytometry. Results: In 2 of 3 gender-mismatched patients we observed limited (5.9% to 6.8% by STR-PCR and 3.5% to 4% by FISH/IHC) engraftment of the bronchial epithelium by exogenous epithelial cells. Engrafting cells were CD34- CD15- CD68- c-Kit-, but expressed CXCR4 on the cell surface. Cells with a similar phenotype were also identified in peripheral blood. In 8 patients, at 2 to 66 months post-transplant, 0.57 ± 0.17% of CD14- peripheral blood mononuclear cells were of epithelial lineage. Almost all were CD45+ and most expressed CXCR4 on the cell membrane. Cells of epithelial lineage were also identified in peripheral blood in healthy individuals but in much lower numbers (0.08 ± 0.01%, p < 0.05). Conclusions: Cells of epithelial lineage are detectable in peripheral blood and are able to engraft the bronchial epithelium in humans. Cell numbers are increased in lung transplantation. Crown Copyright © 2009.